In-situ sulfurized, nitrided and phosphatized modified photoelectrode and preparation method

CN116856000BActive Publication Date: 2026-10-27ANYANG INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310896304.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-21
Publication Date
2026-10-27
Estimated Expiration
2043-07-21

AI Technical Summary

Technical Problem

然而赤铁矿光生电压低,所需要外部偏压大,起始电位大,水界面处存在明显的电位下降,光生载流子的寿命短限制了其进一步应用

Benefits of technology

[0017]本发明以Sn掺杂α-Fe2O3光阳极为基底,然后采用电沉积法制备了FTO/Sn@α-Fe2O3/FeOOH光阳极,最后通过硫化/氮化/磷化处理FTO/Sn@α-Fe2O3/FeOOH光阳极,构建过渡金属硫族化合物与N/P金属络合物组合新型催化剂。扫描电子显微镜(SEM)可以看出光阳极材料的形貌变化,厚度大致为~500nm,从紫外吸收光谱图可以看出吸收率基本保持不变。与Sn@α-Fe2O3薄膜光电流密度(0.88mA/cm2)相比,FTO/Sn@α-Fe2O3/FeOOH/TU/PDP光阳极材料光电流密度(3.38mA/cm2)增大了3.84倍,在电化学测试过程中加入空穴清除剂H2O2,可以结合吸收率计算出转移效率和分离效率均得到提高。光电化学分解水性能的增强主要归因于硫化、氮化和磷化表面处理过程中与光阳极表面FeOOH发生反应,在表面引入了元素S、N、P掺杂,提高导电性,优化载流子输运路径,降低了表面光生载流子的输运阻力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116856000B_ABST
    Figure CN116856000B_ABST
Patent Text Reader

Abstract

The application discloses an in-situ sulfurization, nitridation and phosphatization modified photoelectrode and a preparation method, and belongs to the field of photoelectrochemistry. Firstly, a catalyst FeOOH modified hematite photoelectrode is prepared by using hydrothermal and electrodeposition, and then a composite photoanode material which is subjected to in-situ sulfurization, nitridation and phosphatization treatment is prepared by combining the advantages of chalcogenides and metal coordination complexes. The photoelectrode modified by different catalysts is constructed by changing the concentration and time of sulfurization / nitridation / phosphatization in the solution and other parameters. The oxide photoelectrode is subjected to sulfurization, nitridation and phosphatization treatment in the application, the thickness and loading degree of the catalyst support layer growing on the surface of the hematite photoanode are effectively controlled, the surface defects and recombination are reduced, and the carrier separation efficiency and photoelectrochemical performance of the oxide thin film photoelectrode are significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of photoelectrochemistry and relates to a method for in-situ sulfidation / nitridation / phosphorization modification of photoelectrodes, particularly to the separation and transfer of photogenerated carriers and their application in the field of photoelectrochemical water splitting (PEC-WS). Background Technology

[0002] In recent years, the photoelectrochemical (PEC) splitting of water into hydrogen and oxygen has attracted widespread attention and has become one of the effective strategies for addressing the current energy and environmental crisis. However, the slow water oxidation kinetics and low photoelectric conversion efficiency of most photoelectrode materials limit their practical application. Oxide semiconductors have gained widespread attention due to their tunable chemical composition and controllable band structure. Hematite, an n-type semiconductor with high stability, has been proven to be an ideal candidate photoelectrode material for photoelectrochemical water splitting (PEC-WS). However, hematite's low photogenerated voltage, high required external bias, high onset potential, significant potential drop at the water interface, and short photogenerated carrier lifetime limit its further application. Surface modification of the hematite photoanode (such as introducing a passivation layer, loading an oxygen evolution catalyst, or in-situ surface treatment) can effectively reduce the external bias and onset potential of photodriven water splitting and extend the carrier lifetime, thereby improving the performance of the hematite photoelectrode in PEC-WS.

[0003] Transition metal chalcogenides (S and Se) have attracted widespread attention as promising OER catalysts due to their unique electronic structures. Compared to ordinary metal oxides / hydroxides, the sulfides formed after transformation have a larger electrochemical specific surface area, and the residual S or Se elements on the oxide / hydroxide surface further reduce the water adsorption free energy, thereby improving OER activity. Nitrogen and phosphorus metal coordination complexes, due to their high catalytic activity and diverse structures, have become the most attractive choice for preparing catalyst layers. For example, urea hydrolysis can make the product precipitation more uniform, and it can also act as a reducing agent, dopant, and precipitant, playing a crucial role in the electronic structure and morphology of the catalyst. Summary of the Invention

[0004] This invention, based on the concept of in-situ surface modification to regulate carrier transport, proposes to improve the photoelectrochemical water splitting performance of photoelectrode materials by treating photoelectrodes with in-situ sulfidation, nitridation, and phosphating. First, a hematite photoelectrode modified with the catalyst FeOOH was prepared using hydrothermal and electrodeposition methods. Then, combining the advantages of chalcogenides and metal coordination complexes, a composite photoanode material treated with in-situ sulfidation, nitridation, and phosphating was prepared. Photoelectrodes modified with different catalysts were constructed by changing parameters such as the concentration and time of sulfidation / nitridation / phosphating in the solution. This invention effectively controls the thickness and loading of the co-catalyst layer on the hematite photoanode surface through sulfidation, nitridation, and phosphating treatments on the oxide photoelectrode, reducing surface defects and recombination, and significantly improving the carrier separation efficiency and photoelectrochemical performance of the oxide thin-film photoelectrode.

[0005] The photoelectrode modified by in-situ sulfidation / nitridation / phosphating according to the present invention comprises, from bottom to top: an FTO substrate, an oxide film, a surface catalyst film, and films treated with sulfidation, nitridation, and phosphating.

[0006] Furthermore, in the above technical solution, the oxide thin film is selected from any one of α-Fe2O3, ZnO, WO3, Cu2O, or TiO2. These oxide thin film semiconductors can all be used as photoelectrodes.

[0007] Furthermore, in the above technical solution, the catalyst film is selected from FeOOH, NiOOH, or Co-Pi. The thickness of the catalyst film affects the photoelectrochemical water splitting performance of the semiconductor.

[0008] Furthermore, in the above technical solution, the oxide film is obtained by hydrothermal method, atomic layer deposition method, and ultrasonic spray pyrolysis method; the catalyst film is obtained by atomic layer deposition, electrodeposition, and photodeposition.

[0009] Furthermore, in the above technical solutions, in-situ sulfidation / nitriding / phosphating improves the structure of the photoelectrode surface, such as... Figure 1 As shown.

[0010] The present invention discloses a method for preparing a photoelectrode modified by sulfidation / nitridation / phosphating, comprising the following steps: using FTO / Sn@α-Fe2O3 as a substrate, a FeOOH-modified hematite photoanode is subjected to sulfidation, nitridation and phosphating treatments to obtain a photoelectrode modified by sulfidation, nitridation and phosphating.

[0011] Furthermore, in the above technical solution, an oxide film is prepared by hydrothermal method using FTO as substrate, FeOOH is prepared by surface electrodeposition on the oxide surface, and then it is immersed in thiourea (TU) or urea (UR) or potassium dihydrogen phosphate (PDP) solution for sulfidation, nitriding and phosphating treatment.

[0012] Furthermore, in the above technical solution, the catalyst modification is achieved by using hydrothermal method and electrodeposition method. By controlling the oxide film thickness, the number of electrodeposition layers, etc., surface catalyst-modified photoelectrodes with different excellent photoelectrochemical water splitting performance are obtained.

[0013] Furthermore, in the above technical solution, the photoelectrode is grown using FTO as a conductive substrate.

[0014] The present invention further provides the application of the above-mentioned in-situ sulfidation / nitridation / phosphorization modified photoelectrode in photoelectrochemical water splitting.

[0015] In this experiment, FTO / Sn@α-Fe2O3 / FeOOH photoanodes were prepared using hydrothermal and electrodeposition methods. The effects of varying sulfidation / nitriding / phosphorization treatment times and concentrations on photoelectrode materials with good catalytic performance were investigated. The influence of sulfidation / nitriding / phosphorization treatment of FTO / Sn@α-Fe2O3 / FeOOH photoanodes on the photoelectrochemical water splitting performance was explored, constructing a novel catalyst combining transition metal chalcogenides and N / P metal complexes. In this experiment, FeOOH films were formed on the surface of α-Fe2O3 films via electrodeposition. Sulfidation / nitriding / phosphorization treatment of the FTO / Sn@α-Fe2O3 / FeOOH films on this surface formed S, N, and P composite catalysts, reducing surface defects, effectively improving conductivity, lowering the transport resistance of photogenerated carriers, and improving separation rate and transfer efficiency by altering interfacial charge transfer, binding energy, and internal electric field.

[0016] Technical effect

[0017] This invention uses a Sn-doped α-Fe₂O₃ photoanode as a substrate, and then prepares an FTO / Sn@α-Fe₂O₃ / FeOOH photoanode by electrodeposition. Finally, the FTO / Sn@α-Fe₂O₃ / FeOOH photoanode is treated with sulfidation / nitridation / phosphating to construct a novel catalyst combining a transition metal chalcogenide and an N / P metal complex. Scanning electron microscopy (SEM) reveals morphological changes in the photoanode material, with a thickness of approximately ~500 nm. The UV absorption spectrum shows that the absorbance remains essentially unchanged. The photocurrent density of the Sn@α-Fe₂O₃ thin film is 0.88 mA / cm². 2 Compared to FTO / Sn@α-Fe2O3 / FeOOH / TU / PDP photoanode material, the photocurrent density is 3.38 mA / cm². 2The efficiency increased by 3.84 times. During electrochemical testing, the addition of hole scavenger H2O2 improved both transfer and separation efficiencies, which could be calculated from the absorption rate. The enhanced photoelectrochemical water splitting performance is mainly attributed to the reaction between the sulfidation, nitriding, and phosphating surface treatments and the FeOOH on the photoanode surface. This process introduced S, N, and P doping into the surface, improving conductivity, optimizing carrier transport paths, and reducing the transport resistance of photogenerated carriers. Attached Figure Description

[0018] Figure 1 Schematic diagram of α-Fe2O3 photoanode material treated with sulfidation / nitridation / phosphating; where: FTO represents the growth substrate, α-Fe2O3 represents the semiconductor thin film, and FeOOH represents the surface catalyst and the catalyst after sulfidation, nitridation, and phosphating treatment;

[0019] Figure 2 Top view of FTO / Sn@α-Fe2O3 photoanode material using a scanning electron microscope (SEM);

[0020] Figure 3 Top view of FTO / Sn@α-Fe2O3 / FeOOH photoanode material using a scanning electron microscope (SEM);

[0021] Figure 4 Top view of FTO / Sn@α-Fe2O3 / FeOOH / TU photoanode material using a scanning electron microscope (SEM);

[0022] Figure 5 Top view of FTO / Sn@α-Fe2O3 / FeOOH / TU / PDP photoanode material using scanning electron microscopy (SEM);

[0023] Figure 6 UV-vis spectra of FTO / Sn@α-Fe2O3, FTO / Sn@α-Fe2O3 / FeOOH, FTO / Sn@α-Fe2O3 / FeOOH / TU and FTO / Sn@α-Fe2O3 / FeOOH / TU / PDP photoanode materials;

[0024] Figure 7 X-ray diffraction (XRD) spectra of FTO / Sn@α-Fe2O3, FTO / Sn@α-Fe2O3 / FeOOH, FTO / Sn@α-Fe2O3 / FeOOH / TU and FTO / Sn@α-Fe2O3 / FeOOH / TU / PDP photoanode materials;

[0025] Figure 8JV diagrams of FTO / Sn@α-Fe2O3, FTO / Sn@α-Fe2O3 / TU-30s, FTO / Sn@α-Fe2O3 / TU-60s, and FTO / Sn@α-Fe2O3 / TU-5min photoanode materials at different voltages;

[0026] Figure 9 JV diagrams of FTO / Sn@α-Fe2O3, FTO / Sn@α-Fe2O3 / UR-30s, FTO / Sn@α-Fe2O3 / UR-60s, and FTO / Sn@α-Fe2O3 / UR-5min photoanode materials at different voltages;

[0027] Figure 10 JV diagrams of FTO / Sn@α-Fe2O3, FTO / Sn@α-Fe2O3 / PDP-30s, FTO / Sn@α-Fe2O3 / PDP-60s and FTO / Sn@α-Fe2O3 / PDP-5min photoanode materials at different voltages;

[0028] Figure 11 JV diagrams of FTO / Sn@α-Fe2O3, FTO / Sn@α-Fe2O3 / FeOOH, FTO / Sn@α-Fe2O3 / FeOOH / TU, and FTO / Sn@α-Fe2O3 / FeOOH / TU / PDP photoanode materials under different voltages are shown. Compared with the pure FTO / Sn@α-Fe2O3 photoanode material, the optimal photoanode material FTO / Sn@α-Fe2O3 / FeOOH / TU / PDP achieves a photocurrent density of 3.38 mA / cm² after introducing the surface catalyst FeOOH and performing in-situ S, N, and P treatments on the Sn@α-Fe2O3 photoanode material. 2 The photocurrent density has increased;

[0029] Figure 12 JT plots of FTO / Sn@α-Fe2O3, FTO / Sn@α-Fe2O3 / FeOOH, FTO / Sn@α-Fe2O3 / FeOOH / TU, and FTO / Sn@α-Fe2O3 / FeOOH / TU / PDP photoanode materials at different transient times; compared to the pure FTO / Sn@α-Fe2O3 photoanode material, the optimal FTO / Sn@α-Fe2O3 / FeOOH / TU / PDP photoanode material achieves a photocurrent density of 3.38 mA / cm². 2 It can be seen that the photoelectrocatalytic performance has been improved, and the change pattern is consistent with the JV curve;

[0030] Figure 13FTO / Sn@α-Fe2O3, FTO / Sn@α-Fe2O3 / FeOOH, FTO / Sn@α-Fe2O3 / FeOOH / TU, and FTO / Sn@α-Fe2O3 / FeOOH / TU / PDP photoanode materials at 1.23V RHE The photoelectrochemical impedance spectroscopy (EIS) showed that the transmission resistance of the photoanode material decreased after introducing the surface catalyst FeOOH and the elemental doping S, N, and P on the Sn@α-Fe2O3 surface.

[0031] Figure 14 FTO / Sn@α-Fe2O3, FTO / Sn@α-Fe2O3 / FeOOH, FTO / Sn@α-Fe2O3 / FeOOH / TU, and FTO / Sn@α-Fe2O3 / FeOOH / TU / PDP photoanode materials at 1.23V RHE The following is a Mott-Schottky diagram; after introducing the surface catalyst FeOOH and elemental doping S, N, and P onto the Sn@α-Fe2O3 surface, the donor concentration N of the FTO / Sn@α-Fe2O3 / FeOOH / TU / PDP photoanode material is shown. D The value has reached its maximum. Detailed Implementation

[0032] To more clearly illustrate this technical solution, the following description, in conjunction with the accompanying drawings and embodiments, further illustrates the following: All photoanode materials are developed on an α-Fe₂O₃ substrate. Common preparation methods are as follows: First, the FTO conductive material is ultrasonically washed sequentially with anhydrous ethanol, acetone, and deionized water for 15 minutes, and then dried at 60°C. The FTO conductive material is then adhered to a glass slide with conductive adhesive and fixed at a 45° angle in a PTFE-lined container with the conductive side facing down to facilitate film growth. A clean beaker is used to weigh out FeCl₃ (4.5 mmol) and urea (4.5 mmol) and mix them in 50 mL of deionized water, then ultrasonically dissolved. The resulting homogeneous solution is poured into the PTFE-lined container and placed in an oven at 100°C for 12 hours to obtain FTO / FeOOH. The solution is rinsed with deionized water, immersed in a 0.1 mol / L SnCl₄ ethanol solution for 10 minutes, rinsed again, and dried in an oven at 60°C. The annealing program is set to 500°C for 2 hours and 680°C for 15 minutes. The FTO / Sn@α-Fe2O3 substrate was finally obtained. 2.5 mmol FeCl3, 2.5 mmol NH4F, and 0.05 mmol KCl were dissolved in 100 mL distilled water to form a homogeneous mixed solution. Then, 1.5 mL of H2O2 was added. Cyclic voltammetry (CV) was used with a scanning voltage range of -0.49 V to 0.41 V, a scanning rate of 0.2 V / s, and 1, 3, 5, and 7 scan cycles to prepare FTO / Sn@α-Fe2O3 / FeOOH. Electrochemical tests showed that FTO / Sn@α-Fe2O3 / FeOOH-5 exhibited the best performance.

[0033] 100 mL of 0.1 mol / L thiourea solution was prepared. FTO / Sn@α-Fe₂O₃ / FeOOH samples were immersed in the prepared thiourea solution for 30 s, 60 s, and 5 min to obtain FTO / Sn@α-Fe₂O₃ / FeOOH / TU samples. These FTO / Sn@α-Fe₂O₃ / FeOOH / TU samples were then immersed in 0.1 mol / L potassium dihydrogen phosphate solution. By varying the immersion time, the optimal performance of the FTO / Sn@α-Fe₂O₃ / FeOOH / TU / PDP photoanode material was obtained. The prepared samples are shown below. Figure 1 As shown. From Figure 2 The SEM morphology of the FTO / Sn@α-Fe2O3 photoelectrode can be seen, which is specifically a nanopillar array with a thickness of ~500nm.

[0034] like Figure 3 This reflects the electrodeposition growth of a FeOOH thin film by Sn@α-Fe2O3 photoelectrode, with a surface composed of nanoparticles. Sulfurization was performed using a sulfur source (thiourea) via an immersion method. The morphology of the FTO / Sn@α-Fe2O3 / FeOOH / TU is shown in the figure. Figure 4 .like Figure 5 As shown, the FTO / Sn@α-Fe2O3 / FeOOH / TU photoanode material underwent further phosphating treatment, and scanning electron microscopy (SEM) revealed minimal morphological changes. Figure 6 The image shows the ultraviolet absorption spectrum of the photoanode material, revealing an absorption peak value (η) in the electrodeposited FeOOH film. abs It has clearly become larger. For example... Figure 7 As shown, the X-ray diffraction (XRD) spectra of FTO / Sn@α-Fe2O3, FTO / Sn@α-Fe2O3 / FeOOH, FTO / Sn@α-Fe2O3 / FeOOH / TU and FTO / Sn@α-Fe2O3 / FeOOH / TU / PDP photoanode materials were analyzed, and the appearance of other diffraction peaks can be seen from the figure.

[0035] like Figure 8 The JV diagrams for the photoanode materials FTO / Sn@α-Fe2O3, FTO / Sn@α-Fe2O3 / TU-30s, FTO / Sn@α-Fe2O3 / TU-60s, and FTO / Sn@α-Fe2O3 / TU-5min are shown under different voltages. Compared to FTO / Sn@α-Fe2O3, the photocurrent density of FTO / Sn@α-Fe2O3 / TU-60s reaches its maximum value of 2.36 mA / cm². 2 .like Figure 9 JV diagrams of nitrided photoanode materials (FTO / Sn@α-Fe2O3, FTO / Sn@α-Fe2O3 / UR-30s, FTO / Sn@α-Fe2O3 / UR-60s, FTO / Sn@α-Fe2O3 / UR-5min) at different voltages are shown. Compared to FTO / Sn@α-Fe2O3, the photocurrent density of nitrided FTO / Sn@α-Fe2O3 / UR-60s reaches a maximum of 2.33 mA / cm². 2 .like Figure 10 The JV diagrams for FTO / Sn@α-Fe2O3, FTO / Sn@α-Fe2O3 / PDP-30s, FTO / Sn@α-Fe2O3 / PDP-60s, and FTO / Sn@α-Fe2O3 / PDP-5min photoanode materials under different voltages are shown. Compared to FTO / Sn@α-Fe2O3, the phosphating treatment of FTO / Sn@α-Fe2O3 / PDP-60s resulted in a maximum photocurrent density of 1.18 mA / cm². 2 .like Figure 11The photocurrent density of FTO / Sn@α-Fe2O3, FTO / Sn@α-Fe2O3 / FeOOH, FTO / Sn@α-Fe2O3 / FeOOH / TU, and FTO / Sn@α-Fe2O3 / FeOOH / TU / PDP photoanode materials under a certain voltage range was analyzed. The photocurrent density of the photoanode materials with FeOOH surface catalyst and those with S, N, and P surface treatments reached 3.38 mA / cm². 2 .

[0036] like Figure 12 The Jt plot reflects the transient photocurrent density change over time, consistent with the aforementioned JV curve. Compared to FTO / Sn@α-Fe2O3, the photocurrent density shows an increasing trend after introducing the surface catalyst FeOOH and surface doping with elements S, N, and P. Figure 13 The impedance diagrams (EIS) of the FTO / Sn@α-Fe2O3, FTO / Sn@α-Fe2O3 / FeOOH, FTO / Sn@α-Fe2O3 / FeOOH / TU and FTO / Sn@α-Fe2O3 / FeOOH / TU / PDP photoanode materials tested at 1.23V show a decreasing trend in resistance.

[0037] like Figure 14 As shown, the Mott-Schottky curves of the FTO / Sn@α-Fe2O3, FTO / Sn@α-Fe2O3 / FeOOH, FTO / Sn@α-Fe2O3 / FeOOH / TU, and FTO / Sn@α-Fe2O3 / FeOOH / TU / PDP photoanode materials reflect the donor concentration N of each photoanode material. D The value shows a decreasing trend.

[0038] The above data fully demonstrate the feasibility of this scheme. Sulfidation, nitriding, and phosphating treatments effectively improve the photocurrent density within the Sn-doped α-Fe₂O₃ photoanode material. This scheme is carried out on a Sn-doped α-Fe₂O₃ photoelectrode. First, an FTO / FeOOH film is prepared by hydrothermal synthesis, then immersed in a 0.1 mol / L tin tetrachloride ethanol solution, followed by high-temperature annealing to obtain the Sn-doped α-Fe₂O₃ photoelectrode. A layer of FeOOH is grown through five cycles of electrodeposition, and then subjected to sulfidation, nitriding, and phosphating treatments by immersion in 0.1 mol / L thiourea and potassium dihydrogen phosphate solutions, respectively. Electrochemical tests show a significant increase in photocurrent density. The consistency of the above series of photoelectrochemical tests indicates a significant improvement in PEC-WS performance, with reduced transport resistance and enhanced carrier transport and transfer rates.

[0039] The above embodiments describe the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the present invention. Various changes and modifications can be made to the present invention without departing from its principles, and all such changes and modifications fall within the scope of protection of the present invention.

Claims

1. A method for preparing a photoelectrode modified by in-situ sulfidation and phosphating, characterized in that, Includes the following steps: Using FTO / Sn@α-Fe2O3 as a substrate, 2.5 mmol FeCl3, 2.5 mmol NH4F, and 0.05 mmol KCl were dissolved in 100 mL distilled water to form a homogeneous mixed solution. Then, 1.5 mL H2O2 was added. Cyclic voltammetry was used with a scanning voltage range of -0.49 V to 0.41 V, a scanning rate of 0.2 V / s, and 1, 3, 5, or 7 scan cycles to prepare FTO / Sn@α-Fe2O3 / FeOOH. A 0.1 mol / L thiourea solution was prepared, and FTO / Sn@α-Fe2O3 / FeOOH was immersed in the thiourea solution for 30 s, 60 s, or 5 min to prepare FTO / Sn@α-Fe2O3 / FeOOH / TU. The prepared FTO / Sn@ α-Fe₂O₃ / FeOOH / TU was soaked in 0.1 mol / L potassium dihydrogen phosphate solution to obtain FTO / Sn@α-Fe₂O₃ / FeOOH / TU / PDP.

2. A photoelectrode modified by in-situ sulfidation and phosphating as described in claim 1, characterized in that, The photoelectrode, from bottom to top, consists of: an FTO substrate, a Sn@α-Fe2O3 oxide film, a FeOOH surface catalyst film, and a sulfided and phosphated film.

3. The photoelectrode modified by in-situ sulfidation and phosphating according to claim 2, characterized in that: The oxide film has a thickness of 380-450 nm.

4. The application of the in-situ sulfidated and phosphated modified photoelectrode obtained by the preparation method of claim 1, or the in-situ sulfidated and phosphated modified photoelectrode of claim 2 or 3, in photoelectrochemical water splitting.